Variation of protein MWD parameters and their associations with free asparagine concentration and quality characteristics in hard red spring wheat. (January 2018) - Ohm, Jae-Bom; Simsek, Senay; Mergoum, Mohamed
Abstract: The lower free asparagine concentration (FAC) in wheat is better since it is a precursor to form carcinogenic acrylamide during baking. This research was performed to determine the variations of protein molecular weight distribution (MWD) parameters and the associations of protein MWD parameters with quality characteristics and FAC using eleven hard red spring (HRS) wheat genotypes grown at three locations in North Dakota. Among MWD parameters, the polymeric proteins of SDS unextractable fraction were found to be useful in screening HRS wheat genotypes for low FAC and improvement of bread-making quality characteristics. The ANOVA indicated that growing locations and genotypes significantly (P < 0.01) influenced variation of SDS unextractable polymeric protein parameters while effect of genotype by location interaction was non-significant (P > 0.05). The quantity of SDS unextractable polymeric proteins had significant and positive genotypic correlations (rg ) with quality characteristics including mixograph pattern (rg = 0.87, P < 0.01) and bread loaf volume (rg = 0.86, P < 0.01). The ratio of SDS unextractable polymeric proteins to total protein had a negative correlation with FAC (rg = −0.92, P < 0.01). These results supported the conclusion that the genotypic variations were primarily associated with the significant (P < 0.05) correlations of SDS unextractable polymeric protein parameters with mixograph pattern, bread loaf volume, and FAC. Highlights: Protein MWD, free asparagine concentration (FAC), and quality for HRS wheat. Wheat genotypes showed significant variations for polymeric protein parameters. SDS unextractable polymeric protein had positive effect on bread-making quality. Negative correlation between unextractable polymeric protein parameters and FAC.